Psychological and social consequences of aggravated robberies on victims: evidence from selected precincts in the Eastern Cape - Zondeka, Fikile Michael (Acta criminologica, 2017)
This study examines the psychological and social consequences on victims of aggravated robberies, with the central aim of understanding, from a victim’s perspective, the psychological and social impact of being robbed. In South Africa, there has been a steady increase in aggravated robberies - a phenomenon that has also increased worldwide. The purpose of the research was to explore how aggravated robbery disrupts victims’ core assumption of invulnerability, the ability to handle stress after the incident, as well as the kind of support systems employed to overcome the ordeal. South African citizens, as victims of aggravated robberies, struggle to manage their daily lives. Some aggravated robberies are highly organised by offenders in cases such as cash-in-transit (C-i-T) and bank robberies, as well as the hijacking of vehicles. Other robberies are not as well organised, as is the case with the majority of street robberies. It is worrying when street robberies decrease while and house robberies increase. It is as if the robbers have moved from the street to residential areas. Research data was gathered by means of a survey. Forty-two respondents out of a sample of 1 410 victims, covering all sub-categories of aggravated robberies, were interviewed. Three research sites, namely: East London, KwaZakhele and Mthatha, all in the Eastern Cape Province of South Africa, were selected with all three exhibiting the highest recorded incidences of aggravated robberies in that region. All participants reported some psychological effects during and after the attacks. Because of physical and emotional trauma, specifically where firearms or dangerous weapons were used to threaten the victims, the findings revealed that the impact of aggravated robberies on victims, which accrue in psychological and social consequences followed by Post-Traumatic Stress Disorder (PTSD), is prolonged for a considerable period of time. Due to the financial losses, 98 per cent of the victims exhibited psychological distress and became very intense. Very few participants received any support and most of the victims never received assistance or support from the Government during and/or after the robberies. Based on the research findings, several recommendations are formulated for ways in which victims of aggravated robberies can be assisted, inter alia by making psychologists available at police stations to address a perceived lack of services in this regard.